PENGEMBANGAN VIDEO TUTORIAL SERVIS TUNE UP UNTUK MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN: Pengembangan Video Tutorial Servis Tune Up untuk Mata Pelajaran Pemeliharaan Mesin Kendaraan Ringan - Irfan Eka Prasetya (JURNAL VOKASI DEWANTARA (JVD), 2023)
Learning medium is very influential for students to understand tune up service step in detail. Jobsheet media have several shortcomings such as easily damaged and lost and can not display movement and image in a face. Video tutorials are a learning medium with the use of technology that can be accessed by students easily on the Internet and can cover the shortcomings of jobsheet learning media. The purpose of this research is to produce video tutorials and know their feasibility. This type of research is Research and Development with 5 stages of development, namely: (1) concept, (2) design, (3) collecting, (4) assembly, and (5) testing. The subjects of this study are students of class XI and Teachers of TKR. The object of this research is the medium of video learning. Data collection techniques use observations, interviews and questionnaires, while the research instrument uses a 4-option likert scale questionnaire. Data analysis techniques use quantitative descriptive. The results showed that video tutorial development products were declared worthy of use in learning with an average score score of 41.5 material expert assessments which was 41.5 in the category of very worthy and the assessment of media experts which was 47.5 in the decent category. While in small-scale trials obtained an average score of 71.22 entered into the category of very feasible and large-scale trial assessment of 70.38 entered into the decent category.